Clinical Outcome of Invasive Pituitary Prolactinomas Treated with Cabergoline - Arkawazi, Bassam M Flamerz (AL-Kindy College Medical Journal, 2020)
Background: Treatment of invasive prolactinoma, which has several characteristics including invasive growth into cavernous sinuses and formation of giant adenomas compressing adjacent neural structures, resulting in neurological dysfunction, has been very challenging. There are relatively few reports available describing long-term treatment outcome. Aims of the study: In this study we evaluate the results of cabergoline administration as initial treatment during 4 years follow up period. Methods: We prospectively categorized 36 patients into four groups according to the results of 3 months of cabergoline treatment: group 1, tumor volume reduction (TVR) ˃25% with normalized serum prolactin (NP) (n = 24); group 2, TVR˃25% without NP (n = 4); group 3, TVR ˂25% with NP (n = 5); and group 4, TVR ˂25% without NP (n = 3). Results: During follow-up, 22 patients (91.7%) in group 1 achieved TVR˃50% with NP. Three patients (75%) in group 2 achieved TVR˃50% with NP after treatment for 8 months. In group 3, four patients (80.0%) continued medication because of improvement of symptoms and achieved additional TVR(18.8–46.4%). Surgery was performed on five patients (one in group 2, one in group 3, and three in group 4), and complete resection was achieved in four (80.0%). Overall, 25 (69.4%) of the 36 patients treated with cabergoline had complete response and 6 (16.7%) had partial response but did not require surgery. Thus, the overall response rate was 86%,with only five patients (14%) requiring surgical debulking. NP was not achieved by surgery alone in all cases, even after total resection of tumor. Conclusion: Patients who achieve TVR˃25%with NP with 3 months of cabergoline administration had a high possibility of showing good long term response (TVR˃50% with NP) to cabergoline. A higher dose of dopamine agonist (DA) should be considered for patients who achieve TVR˃25% without NP.